Penggunaan Kendaraan Listrik di Indonesia dan Relevansinya dengan Ajaran Konservasi Lingkungan dalam al-Qur’an - Zulkarnain, Muhammad Akbar (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
In the Qur'an, Allah appoints humans as stewards of the earth, entrusted with preserving His creation. However, widespread environmental destruction, including global warming caused by fossil-fuel vehicles, reflects a failure to fulfill this role. These vehicles produce high greenhouse gas emissions, contributing to air pollution and climate change. To address this, the Indonesian government has introduced the Electric Motor Vehicle Acceleration Program, which aims to reduce emissions and conserve resources through the adoption of electric vehicles (EVs). This initiative aligns with the Qur'anic mandate to protect the environment.This study explores electric vehicles as a government-proposed solution to environmental damage, viewed through a Qur'anic lens. Using the maudhui (thematic) method, relevant Qur'anic verses on environmental stewardship are analyzed. Key terms such as "لاتفسد" (do not cause corruption), "لاتبذِر" (do not be wasteful), and "اِصْلَاحِ" (restoration) are examined for their applicability. The findings suggest that transitioning to EVs aligns with these principles, as their low emissions and energy efficiency support environmental preservation. Thus, the program reflects the Qur'anic call for sustainable practices, addressing pollution while promoting the restoration and protection of the natural world.